Snakes and ladders and loaded dice: Poverty dynamics and inequality in South Africa, 2008-2017 - Rocco Zizzamia; Simone Schotte; Murray V. Leibbrandt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Longitudinal surveys can give insight into economic mobility, which allows us to understand how markers of (dis)advantage are consequential in determining material conditions in the present, and how these markers structure economic opportunity over time. In this paper we show that this dynamic element - the risk of falling into (deeper) poverty and the chances of moving up - looms large in the economic lives of both the poor and the non-poor in South Africa. We use all five waves of available National Income Dynamics Study data to provide a thorough and up-to-date analysis of poverty dynamics in South Africa between 2008 and 2017. This analysis focuses on the correlates of transitions into and out of poverty, and investigates how multidimensional inequalities in terms of household- and individual-level characteristics relate to both poverty persistence and vulnerability to poverty. We also update our 2018 analysis using NIDS Wave 5 data to directly link the dynamic study of poverty to the dynamic study of inequality through the lens of social stratification.
Keywords: D63; D310; O12; O15; 330; inequality; poverty; poverty dynamics; South Africa; social stratification; panel data